From Motivation to Sustained Engagement: A Dual-Process Framework of Self-Regulation in Physical Literacy. A Systematic Review - Rusmitaningsih, Fika Nuraini; Ma’mun, Amung; Juliantine, Tite; Sucipto, Sucipto; Gustian, Uray (Physical Education Theory and Methodology, 2026)
Background. Physical literacy (PL) has emerged as a central outcome of contemporary physical education, reflecting a shift toward holistic approaches that integrate physical, cognitive, and affective domains. However, existing research often examines motivational and behavioral factors in isolation, limiting understanding of how sustained engagement in physical activity develops. Objectives. This study aims to provide a thematically grounded synthesis of how non-cognitive attributes and self-regulatory processes interact to shape physical literacy outcomes in educational contexts. Materials and Methods. A systematic review was conducted following PRISMA 2020 guidelines. Literature was retrieved from the Scopus and Web of Science databases using predefined search criteria. A total of 36 studies met the inclusion criteria and were analyzed using thematic synthesis. Results. Four key themes were identified: (1) non-cognitive foundations, (2) self-regulatory mechanisms, (3) pedagogical and social contexts, and (4) digital and hybrid learning pathways. The findings indicate a consistent pattern in which non-cognitive attributes—particularly motivation, confidence, and self-efficacy—function as initiators of engagement, while sustained participation is supported by self-regulatory processes such as goal-setting, self-monitoring, and behavioral adjustment. These processes facilitate the transition from initial intention to more stable participation over time. In addition, pedagogical and digital contexts shape this relationship by structuring and supporting the interaction between motivational and regulatory processes. Conclusions. The findings support a dual-process perspective in which motivation initiates engagement and self-regulation stabilizes behavior over time. This study contributes by clarifying how engagement in physical activity can be both initiated and sustained, providing a basis for designing physical education programs that integrate motivational and self-regulatory development.